Effects of a mutated yeast plus addition of sucrose and nitrogen on the total higher alcohol levels of a plum wine fermentation. Issue 4 (26th September 2014) - Zhen, Da; Lv, Mei; Chen, Maobin; Luo, Junjie; Liu, Dongqi
<x xml:space="preserve">Abstract</x> The brewing process and strain employed can play key roles in controlling the level of total higher alcohols (THA) in plum wine. In this study, fermentations using Saccharomyces cerevisiae XN3 and plum must led to the production of 671 mg/L THA (including 1‐propanol, isobutanol and isopentanol). A mutant of XN3, exhibiting a higher activity of lactic acid dehydrogenase, named XN3‐3, produced lower levels of THA at 538 mg/L. Further optimization of the brewing process, including rapid nitrogen and sugar fed‐batch additions, were conducted with XN3‐3. Tests with the addition of 0.4 g/L (NH4)2HPO4 produced a lower level of THA (385 mg/L) than sucrose additions (to a 20°Brix level) using the fed‐batch method (452 mg/L). These additions were effective in reducing the higher alcohols and could be combined in application. Copyright © 2014 The Institute of Brewing & Distilling